A strategic neurological research agenda for Europe: Towards clinically relevant and patient-centred neurological research priorities - Boon, Paul; Lescrauwaet, Emma; Aleksovska, Katina; Konti, Maria; Berger, Thomas; Leonardi, Matilde; Marson, Tony; Kallweit, Ulf; Moro, Elena; Toscano, Antonio; Rektorova, Irena; Crean, Michael; et al. (European journal of neurology, 2024)
BACKGROUND AND PURPOSE: Neurological disorders constitute a significant portion of the global disease burden, affecting >30% of the world's population. This prevalence poses a substantial threat to global health in the foreseeable future. A lack of awareness regarding this high burden of neurological diseases has led to their underrecognition, underappreciation, and insufficient funding. Establishing a strategic and comprehensive research agenda for brain-related studies is a crucial step towards aligning research objectives among all pertinent stakeholders and fostering greater societal awareness. METHODS: A scoping literature review was undertaken by a working group from the European Academy of Neurology (EAN) to identify any existing research agendas relevant to neurology. Additionally, a specialized survey was conducted among all EAN scientific panels, including neurologists and patients, inquiring about their perspectives on the current research priorities and gaps in neurology. RESULTS: The review revealed the absence of a unified, overarching brain research agenda. Existing research agendas predominantly focus on specialized topics within neurology, resulting in an imbalance in the number of agendas across subspecialties. The survey indicated a prioritization of neurological disorders and research gaps. CONCLUSIONS: Building upon the findings from the review and survey, key components for a strategic and comprehensive neurological research agenda in Europe were delineated. This research agenda serves as a valuable prioritization tool for neuroscientific researchers, as well as for clinicians, donors, and funding agencies in the field of neurology. It offers essential guidance for creating a roadmap for research and clinical advancement, ultimately leading to heightened awareness and reduced burden of neurological disorders.
Keywords: globální zátěž nemocemi; Nervous System Diseases; Global Burden of Disease; neurologie; výzkum; Research; Neurology; Humans; lidé; Europe; Evropa; nemoci nervového systému